Makna Doa Berkat Di Akhir Ibadah Kristen Berdasarkan Bilangan 6:23-27 Dan 2 Korintus 13:13 - Jundo Parasian Siregar (Sekolah Tinggi Teologi Shema Cianjur, 2025)
This study explores the meaning of the prayer of blessing at the end of worship, as practiced by many churches. The prayer of blessing is based on Numbers 6:24-26 and 2 Corinthians 13:13. Previous research found that some prayers of blessing include additional phrases. Furthermore, some prayers are delivered incompletely or in reverse order, not in accordance with the biblical references. Furthermore, the understanding of the person delivering the blessing and the recipient is often out of sync. This paper uses theological research, a qualitative biblical theology approach, because its purpose is to discover the meaning of the biblical text. The results show that the prayer of blessing is